Japanese Millennials and Intersex Awareness - Lusk, Jeniece (2017)
This paper investigates the awareness, attitudes, and opinions of Japanese millennials about intersex people. This research attempts to fill a gap in extant literature concerning the intersex in Asia via an exploratory analysis. The LGBTQ(I) discourse of Japan mimics that of the west; often the "I" is totally disregarded. Here, a snapshot of Japanese millennial awareness is offered using survey results collected from a convenience sample of Japanese college students. Findings suggest that the understanding of what the term “intersex” means is limited. An interesting argument addressing the differential treatment of one’s sex versus one’s sexuality via queering is offered, alongside proposals for further exploration using qualitative means should be done in the future. In addition, a comparison to Western awareness and understanding would be an appropriate next step.